Exhaled nitric oxide levels in asthma: Personal best versus reference values - Smith, Andrew D.; Cowan, Jan O.; Taylor, D. Robin (Journal of allergy and clinical immunology, 2009)
Factors affecting the fraction of nitric oxide in exhaled air (FE NO) are multiple. Interpreting values when assessing airways disease may be problematic. Clinically optimum levels have not been defined. We aimed to establish the relationship between predicted values for FE NO obtained from equations by Olin et al, Travers et al, and Dressel et al, and normalized levels after oral prednisone. We also compared postprednisone FE NO levels with those obtained during optimized treatment with inhaled fluticasone. Data were obtained before and after a trial of oral prednisone (30mg/d for 14 days), and also from a previously published study in which patients had their dose of inhaled corticosteroid adjusted using either FE NO or symptoms/lung function to optimize treatment. Seventy-three patients completed the study. The geometric mean FE NO after prednisone (17.7 parts per billion [ppb]; 95% CI, 15.5-20.2) was significantly lower than mean FE NO at the optimized fluticasone dose (20.2 ppb; 95% CI, 17.1-23.8; P=.04) and at loss of control (27.6 ppb; 95% CI, 22.8-33.4; P < .001). FE NO levels after prednisone did not differ significantly from the predicted values of Olin et al (16.8 ppb, 95% CI, 16.0-17.5; P=.44), but were significantly lower than values of Travers et al (predicted, 21.5 ppb; 95% CI, 20.9-22.2; P=.005) and Dressel et al (predicted, 27.8 ppb; 95% CI, 26.7-28.9; P < .001). Optimum FE NO levels are best established by using oral rather than inhaled steroid treatment, and these approximate to predicted values from the reference equation by Olin et al. However, at optimized doses of inhaled corticosteroid, although FE NO levels were higher than predicted, asthma was well controlled. Targeting FE NO on reference values is not justified.